Implementasi program edukasi dan skrining hipertensi berbasis komunitas di desa Penyandingan Kabupaten Ogan Komering Ilir - Siti Nadira Aulia; Raisa Raslina Utama; Reswara Bhanuwati; Salwa Tsabita Hany; Rangga Asnanto; Nadya Az Zahra Darwan; Nabila Nurdita; Tesya Aprilia Kartika (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Hypertension is a non-communicable disease and one of the leading causes of morbidity and mortality in Indonesia. A community-based hypertension education and screening program was implemented in Penyandingan Village, Ogan Komering Ilir Regency, South Sumatra, as an effort to support the early detection of non-communicable disease risk factors. The program included health education on hypertension and health screening through blood pressure measurement and random blood glucose (RBG) testing involving more than 100 participants. The screening results showed that approximately 60% of participants had blood pressure above the normal range, with some classified as having severe hypertension, while several participants also exhibited elevated random blood glucose levels. These findings indicate that hypertension and other non-communicable disease risk factors remain prevalent in the community and highlight the importance of community-based screening for early detection. This program is expected to serve as an initial step toward improving healthcare utilization through follow-up examinations, continuous health education, and strengthened involvement of community health volunteers in hypertension prevention and control.